Comparative Assessment of Dental Caries Using WHO and ICDAS II Criteria in Patients Visiting a Dental Hospital in Kathmandu - Khanal, Sunita; Shrestha , Sujita; Poudel, Shreesti (Journal of Nepalese Association of Pediatric Dentistry, 2024)
Introduction: Being the most common chronic dental disease in the world, dental caries can lead to pain, discomfort and disfigurement. Therefore, its detection is of epidemiologic importance. Previously WHO system was mostly used but now days, International Caries Detection and Assessment System (ICDAS) is being preferred for its improved quality of diagnosis, prognosis, and clinical treatment of caries and dental condition. Objective: The main objective of this study was to compare the caries assessment of WHO and ICDAS system in Patients Visiting a Dental Hospital in Kathmandu Methods: An analytical cross-sectional study was conducted for four months among the patients visiting the department of oral medicine and radiology department of Kantipur Dental College after taking ethical approval from institutional review board of Kantipur Dental College. Informed consent was taken from each patient before the study. A predesigned standard questionnaire was used for the data collection purpose. Descriptive statistics were presented as frequency and percentages and chi square test was done to test the statistically significant difference between the variables. P value ˂0.05 was considered statistically significant. Results: A total of 231 study participants belonging to age group 14-50 years were there out of which 102(44%) were male and 129(56%) were female. The prevalence of caries according to ICDAS and WHO was 95.2% and 92.64% respectively. Comparison of caries assessment using both ICDAS and WHO showed a highly statistically significant difference (p<0.001). Conclusion: Caries prevalence using ICDAS system was more compared to WHO system. ICDAS system can be a better tool compared to WHO system for detecting early carious lesions.